Roles of Peroxisome Proliferator-Activated Receptor β/δ in skeletal muscle physiology - Manickam, Ravikumar (2017)
More than two decades of studying Peroxisome Proliferator-Activated Receptors (PPARs) has led to an understanding of their implications in various physiological processes that are key for health and disease. All three PPAR isotypes, PPARα, PPARβ/δ, and PPARγ, are activated by a variety of molecules, including fatty acids, eicosanoids and phospholipids, and regulate a spectrum of genes involved in development, lipid and carbohydrate metabolism, inflammation, and proliferation and differentiation of many cell types in different tissues. The hypolipidemic and antidiabetic functions of PPARα and PPARγ in response to fibrate and thiazolidinedione treatment, respectively, are well documented. However, until more recently the functions of PPARβ/δ were less well defined, but are now becoming more recognized in fatty acid metabolism, energy expenditure, and tissue repair. Skeletal muscle is an active metabolic organ with high plasticity for adaptive responses to varying conditions such as fasting or physical exercise. It is the major site of energy expenditure resulting from lipid and glucose catabolism. Here, we review the multifaceted roles of PPARβ/δ in skeletal muscle physiology.